The Role and Limits of the Sebalos Customary Institution in Resolving the Bakati Riuk Ulayat Land Dispute with PT Ceria Prima - Ronald Mansye Ufi; Endang Sumiarni; Widiartana Widiartana (CV. Era Digital Nusantara, 2026)
This article examines the role and practical limits of the Sebalos Customary Institution in resolving the ulayat land dispute between the Bakati Riuk customary law community and PT Ceria Prima in Bengkayang Regency, West Kalimantan. The study uses empirical legal research with socio-legal and case-study approaches. Primary data were derived from semi-structured interviews with the head of the customary institution and affected community members, while documentary materials included objection letters, customary deliberation minutes, an investigative-team decree, meeting records, and relevant legislation. The data were organized chronologically, coded thematically, and cross-checked across oral and documentary sources. The findings identify three principal roles: representing community claims before government and the company, organizing customary deliberation, and enforcing customary norms through sanctions and rituals. These roles demonstrate strong internal legitimacy as living law, an expression of volksgeist, and a form of community-based conflict resolution. Their external legal effectiveness, however, remains limited. The principal barriers are the weak binding force of customary decisions against a corporation, the absence of completed formal recognition of the community, incomplete participatory mapping and administrative recording of the disputed territory, unequal bargaining resources, and unresolved tension between customary legitimacy and company reliance on administrative authorization. The article contributes by distinguishing the existence of a socially legitimate customary role from its capacity to produce an enforceable inter-party settlement.